Direct capture and conversion of CO2 from air by growing a cyanobacterial consortium at pH up to 11.2. Issue 7 (8th April 2019) - Ataeian, Maryam; Liu, Yihua; Canon‐Rubio, Karen Andrea; Nightingale, Michael; Strous, Marc; Vadlamani, Agasteswar
Abstract: Bioenergy with carbon capture and storage (BECCS) is recognized as a potential negative emission technology, needed to keep global warming within safe limits. With current technologies, large‐scale implementation of BECCS would compromise food production. Bioenergy derived from phototrophic microorganisms, with direct capture of CO2 from air, could overcome this challenge and become a sustainable way to realize BECCS. Here we present an alkaline capture and conversion system that combines high atmospheric CO2 transfer rates with high and robust phototrophic biomass productivity (15.2 ± 1.0 g/m 2 /d). The system is based on a cyanobacterial consortium, that grows at high alkalinity (0.5 mol/L) and a pH swing between 10.4 and 11.2 during growth and harvest cycles. Abstract : In the photobioreactor unit (PBR), biomass is produced and separated from high pH medium (pH 11.2) at the end of each cycle. Then CO3 2− rich medium is transferred to the carbon capture unit where high atmospheric CO2 transfer rates will increase the HCO3 − concentration and bring the pH down. The HCO3 − rich media then is transferred back to the PBR unit for microalgae cultivation.